Interaction Effect of Gender and Teaching Methods on Students’ Retention in Literary Appreciation - Assimonye, Augusta Chiedu (Teaching, Learning, and Development, 2024)
Students’ poor retention and declining interest in literary appreciation have continued to pose serious challenges to the effective teaching and learning of Literature in English in Nigerian secondary schools. Traditional teaching methods that emphasize teacher-centered instruction often fail to sustain students’ long-term understanding and engagement. This study therefore investigated the interaction effect of gender and teaching methods on students’ retention in literary appreciation among Senior Secondary II students in Anambra State. The study adopted a quasi-experimental design using a pretest and posttest non-equivalent control group. Intact classes were assigned to experimental and control groups, with the experimental group taught through reciprocal peer tutoring and the control group through conventional teaching. Conducted in Anambra State, the study involved 65 Senior Secondary II students drawn from two co-educational schools. Data were collected using the Literature in English Achievement and Retention Test, validated and found reliable with a coefficient of 0.72. Teachers administered pretests, posttests, and retention tests. Data were analyzed using mean, standard deviation, and analysis of covariance at a 0.05 significance level. The findings revealed that male students recorded a posttest mean score of (52.81) and retention mean of (55.61) with a gain of (2.80), while female students had posttest and retention means of (51.47) and (52.58) with a gain of (1.11). This indicated that males achieved slightly higher retention using the conventional method. The ANCOVA result showed a significance value of (0.102), which exceeded the (0.05) level, leading to the acceptance of the null hypothesis. Hence, there was no significant interaction effect of gender and teaching methods on students’ retention in literary appreciation, implying that retention was independent of gender. The study concluded that students’ retention depended more on the teaching strategies employed than on gender differences. It recommended that Literature in English teachers adopt more interactive and student-centered approaches such as Reciprocal Peer Tutoring to enhance understanding and long-term retention in literary studies.